Hydrochemical and toxicological characteristics of the state of the Ural River within the West Kazakhstan region. (Eurasian Journal of Ecology, 2016)
The characterisation of the hydrochemical and toxicological situation of Ural in 2011-2013 seasonal year. The changes in total mineralization, permanganate oxidation, the content of nitrates, nitrites and heavy metalsis showed. A quantitative evaluation of pollutants at Ural river water is given. Transborder pollution, coming to the area on the Ural River with Flood and low flow is calculated. The changes of the chemical compositionof the river. Installed pollution on individual components (copper, zinc, chromium (VI) iron) is given.
Keywords: Ural river; hydrochemical indicators; toxicants; heavy metals; transborder pollution; water ecosystem; anthropogenic impact